Micrometeorological monitoring reveals that canopy temperature is a reliable trait for the screening of heat tolerance in rice - Tian, Wentao; Mu, Qilin; Gao, Yuan; Zhang, Yunbo; Wang, Yi; Ding, Shuangcheng; Aloryi, Kelvin Dodzi; Okpala, Nnaemeka Emmanuel; Tian, Xiaohai (Frontiers in Plant Science, 2024)
Micrometeorological monitoring is not just an effective method of determining the impact of heat stress on rice, but also a reliable way of understanding how to screen for heat tolerance in rice. The aim of this study was to use micrometeorological monitoring to determine varietal differences in rice plants grown under two weather scenarios-Long-term Heat Scenario (LHS) and Normal Weather Scenario (NWS)so as to establish reliable methods for heat tolerance screening. Experiments were conducted with two heat susceptible varieties-Mianhui 101 and IR64-and two heat tolerant varieties, Quanliangyou 681 and SDWG005. We used staggered sowing method to ensure that all varieties flower at the same time. Our results showed that heat tolerant varieties maintained lower canopy temperature compared to heat susceptible varieties, not just during the crucial flowering period of 10 am to 12 pm, but throughout the entire day and night. The higher stomatal conductance rate observed in heat tolerant varieties possibly decreased their canopy temperatures through the process of evaporative cooling during transpiration. Conversely, we found that panicle temperature cannot be used to screen for heat tolerance at night, as we observed no significant difference in the panicle temperature of heat tolerant and heat susceptible varieties at night. However, we also reported that higher panicle temperature in heat susceptible varieties decreased spikelet fertility rate, while low panicle temperature in heat tolerant varieties increased spikelet fertility rate. In conclusion, the results of this study showed that canopy temperature is probably the most reliable trait to screen for heat tolerance in rice.